Websites usability instrument validation using think-aloud method - Ahmad, M. A. B. (2013)
The purpose of this study is to validate the websites usability instrument. The instrument is designed to evaluate Higher Education Institution (HEI) websites. It was only tested on a small scale before so it must be validated first. There are several type of method that can be used to validate the website usability instrument. The method used in this study is the think-aloud method. The literature review in this study will analyse what is the think-aloud method and how it was used from other research that has been conducted. Besides that, other important criteria of the validation procedure will be analyse in order to increase the validity of the websites usability instrument validation results. From the literature review gathered, suitable procedure of the think-aloud method for this study was developed. The think-aloud method was applied in the interview given to the participant and the result from it was used as this study findings. The focus of the validation is to improve the proposed website usability instrument.